Anti-ultraviolet filler, anti-ultraviolet silicone rubber and preparation method and application thereof

By doping Fe elements in TiO2, Fe-doped TiO2 is formed as an ultraviolet-resistant filler, the problem of degradation of silicone rubber under ultraviolet radiation is solved, and the effect of improving the ultraviolet resistance and extending the service life of silicone rubber is achieved.

CN119591934APending Publication Date: 2025-03-11STATE GRID HUNAN ELECTRIC POWER COMPANY LIMITED +3
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411684410.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

When composite insulators are used outdoors, the outer layer of silicone rubber is susceptible to ultraviolet radiation, resulting in reduced insulation performance and mechanical strength and affecting service life.

Method used

A UV-resistant filler is designed to form Fe-doped TiO2 as a strong UV-resistant filler by doping Fe into TiO2 and introducing it into silicone rubber to improve the UV-resistant ability of silicone rubber.

Benefits of technology

It significantly improves the light stability and UV resistance of silicone rubber, extends the service life of composite insulators in outdoor environments, and maintains its excellent mechanical and electrical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005149086700000101
    Figure BDA0005149086700000101
  • Figure BDA0005149086700000111
    Figure BDA0005149086700000111
  • Figure HDA0005149086710000011
    Figure HDA0005149086710000011
Patent Text Reader

Abstract

The invention relates to an anti-ultraviolet filler, anti-ultraviolet silicone rubber and a preparation method and application of the anti-ultraviolet filler and the anti-ultraviolet silicone rubber. And the component of the anti-ultraviolet filler is Fe-doped TiO2 (titanium dioxide). The preparation method of the anti-ultraviolet filler comprises the following steps: adding soluble ferric salt into a mixed solvent of glacial acetic acid, absolute ethyl alcohol and deionized water to obtain a first solution; uniformly mixing butyl titanate with absolute ethyl alcohol to obtain a second solution; dropwise adding the first solution into the second solution, and stirring to obtain gel; and drying and calcining the gel to obtain the anti-ultraviolet filler. The preparation method of the anti-ultraviolet silicone rubber comprises the following steps: mixing methyl vinyl silicone raw rubber, aluminum hydroxide micro powder and fumed silica to obtain mixed base rubber; mixing the mixed base rubber, an anti-ultraviolet filler, hydrogen-containing silicone oil and a coupling agent to obtain mixed rubber; performing vulcanization reaction on the mixed rubber and a vulcanizing agent to obtain the anti-ultraviolet silicone rubber. The uvioresistant silicone rubber provided by the embodiment of the invention has strong uvioresistant performance and excellent mechanical and electrical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to an anti-ultraviolet filler, an anti-ultraviolet silicone rubber, and a preparation method and application thereof. Background Art

[0002] When composite insulators are used outdoors, the outer layer of silicone rubber is susceptible to ultraviolet radiation, which can cause the silicone rubber's microscopic molecular chains to break, surface cracks, and filler precipitation, thereby reducing its insulation performance and mechanical strength, and shortening its service life.

[0003] Common measures to improve UV resistance include increasing the raw rubber content or adding UV absorbers. Although increasing the raw rubber content can enhance UV resistance, it reduces the arc resistance of silicone rubber and makes it easily damaged under high voltage. Therefore, new UV resistant fillers need to be explored. Adding UV absorbers has problems such as toxicity, poor stability and easy migration in polymers.

[0004] Therefore, designing an anti-UV silicone rubber with high efficiency anti-UV ability and excellent mechanical and electrical properties has become a research trend. Summary of the invention

[0005] In order to solve at least one of the above technical problems, the present invention provides an anti-ultraviolet filler, an anti-ultraviolet silicone rubber, and a preparation method and application thereof.

[0006] As one aspect, the present invention provides an anti-UV filler, the component of which is Fe-doped TiO2; the particle size of the anti-UV filler is 30 to 50 nm; wherein, in the anti-UV filler, the molar ratio of iron element to titanium element is in the range of (0.2 to 2):100.

[0007] As another aspect, the present invention provides a method for preparing the above-mentioned anti-UV filler, and the method for preparing the anti-UV filler comprises: adding a soluble iron salt to a mixed solvent of glacial acetic acid, anhydrous ethanol and deionized water to obtain a first solution; uniformly mixing butyl titanate and anhydrous ethanol to obtain a second solution; dropwise adding the first solution to the second solution and stirring until a uniform and transparent TiO2 sol is formed, and aging at room temperature to obtain a gel; and drying and calcining the gel to obtain the anti-UV filler.

[0008] In some embodiments of the present invention, the molar ratio of iron in the soluble iron salt to titanium in butyl titanate is in the range of (0.2-2):100; and / or, in the first solution, the volume ratio of glacial acetic acid, anhydrous ethanol and deionized water is in the range of (7-8):(4-5):1; and / or, the concentration of iron in the soluble iron salt in the first solution is 0.0004-0.6 mol / L; and / or, in the second solution, the volume ratio of butyl titanate to anhydrous ethanol is in the range of (1:6)-(3:6).

[0009] In some embodiments of the present invention, the soluble iron salt is ferric nitrate or ferric chloride; and / or the aging time is 20 to 24 hours; and / or the drying condition of the gel is: drying at 50 to 80° C. for 24 to 36 hours; and / or the calcination condition is: calcining at 900 to 1000° C. for 2 to 4 hours.

[0010] As another aspect, the present invention provides an anti-UV silicone rubber, which comprises the anti-UV filler mentioned above or the anti-UV filler obtained by the above preparation method.

[0011] In some embodiments of the present invention, the raw materials for preparing the anti-ultraviolet silicone rubber include, by mass, 5 to 10 parts of anti-ultraviolet filler, 75 to 110 parts of methyl vinyl silicone rubber, 25 to 45 parts of fumed silica, 110 to 140 parts of aluminum hydroxide powder, 1 to 3 parts of hydrogenated silicone oil, 1 to 5 parts of coupling agent and 1 to 3 parts of vulcanizing agent.

[0012] In some embodiments of the present invention, the vulcanizing agent is a dipentadienyl vulcanizing agent; and / or the coupling agent is KH560; and / or the molecular weight of the methyl vinyl silicone rubber is 600,000 to 660,000, and the vinyl content is 0.16 to 0.22%; and / or the specific surface area of ​​the fumed silica is 220 to 250 m 3 / g; and / or, the particle size of the aluminum hydroxide powder is 6000-7000 mesh; and / or, the hydrogen concentration of the hydrogen-containing silicone oil is greater than 0.5%.

[0013] As another aspect, the present invention provides a method for preparing the above-mentioned anti-UV silicone rubber, and the preparation method of the anti-UV silicone rubber includes: mixing methyl vinyl silicone raw rubber, aluminum hydroxide powder and fumed silica to obtain a mixed base rubber; mixing the mixed base rubber, anti-UV filler, hydrogen-containing silicone oil and a coupling agent to obtain a mixed rubber; subjecting the mixed rubber to a vulcanizing agent for a vulcanization reaction to obtain an anti-UV silicone rubber; wherein the anti-UV filler is the above-mentioned anti-UV filler or an anti-UV filler obtained using the above-mentioned preparation method.

[0014] In some embodiments of the present invention, the method of mixing methyl vinyl silicone rubber, aluminum hydroxide powder and fumed silica is kneading with a kneader at a temperature of 135 to 160°C and a kneading time of 3 to 5 hours; and / or, the method of mixing the mixed base rubber, anti-UV filler, hydrogen-containing silicone oil and coupling agent is kneading with a kneader at a temperature of 140 to 160°C and a kneading time of 2 to 3 hours; and / or, the pressure of the mixed rubber and the vulcanizing agent for the vulcanization reaction is 10 to 15 MPa, the temperature is 140 to 160°C, and the time is 10 to 15 minutes.

[0015] As another aspect, the present invention provides a use of the above-mentioned UV-resistant silicone rubber or the UV-resistant silicone rubber obtained by the above-mentioned method for preparing the UV-resistant silicone rubber in preparing a composite insulator.

[0016] The technical solution provided by the embodiment of the present invention has the following advantages:

[0017] The anti-ultraviolet filler of the embodiment of the present invention improves the absorption rate of ultraviolet light by doping Fe into TiO2. Specifically, TiO2 is a typical wide bandgap semiconductor material with a bandgap width of 3.2eV, which determines that it can only absorb ultraviolet light with a wavelength less than 387nm, and has a very low absorption rate for the visible light part that accounts for a larger proportion of sunlight (ultraviolet light below 400nm). By doping with Fe elements, new energy levels can be introduced, which are located between the valence band and the conduction band of TiO2, forming intermediate energy levels or impurity energy levels. The presence of these intermediate energy levels enables TiO2 to absorb photons with lower energy, thereby widening the light absorption range and enhancing the absorption rate of ultraviolet light.

[0018] The anti-ultraviolet silicone rubber of the present invention effectively improves the anti-ultraviolet ability of the silicone rubber by introducing Fe-doped TiO2 as a strong anti-ultraviolet filler. Specifically, the doping of Fe improves the electronic structure of TiO2 and expands its light absorption range, thereby significantly improving the light stability and anti-ultraviolet efficiency of the silicone rubber. This helps to extend the service life of the composite insulator in an outdoor environment and reduce the material aging problem caused by ultraviolet radiation.

[0019] The anti-ultraviolet silicone rubber of the present invention not only ensures the strong anti-ultraviolet performance of silicone rubber, but also maintains its excellent mechanical and electrical properties. By optimizing the raw material ratio and preparation process, the mechanical strength and insulation performance requirements of the composite insulator in practical applications are met, and it is suitable for long-term use in a strong ultraviolet harsh environment.

[0020] The preparation method of the anti-ultraviolet silicone rubber of the present invention is simple and easy, and can efficiently produce strong anti-ultraviolet silicone rubber with excellent performance through reasonable stirring, mixing and vulcanization processes, and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0023] Figure 1 A comparison diagram of the atomic structure of the anti-ultraviolet filler (Fe-doped TiO2) prepared in an embodiment of the present invention and the atomic structure of TiO2;

[0024] Figure 2 This is a comparison chart of the absorbance of the anti-ultraviolet filler (Fe-doped TiO2) and TiO2 in the ultraviolet range prepared in an embodiment of the present invention. DETAILED DESCRIPTION

[0025] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0026] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.

[0027] Titanium dioxide has excellent ultraviolet absorption and scattering properties as an anti-ultraviolet filler, but its anti-ultraviolet ability is still limited in strong ultraviolet environments. Doping with metal elements can improve the electronic structure of TiO2 and expand its light absorption range. Doped TiO2 can effectively reduce the recombination of photogenerated electrons and holes while absorbing ultraviolet rays, thereby improving photostability and anti-ultraviolet efficiency. Introducing doped TiO2 into the silicone rubber matrix can significantly enhance the anti-ultraviolet ability of silicone rubber and extend its outdoor service life while ensuring its arc resistance. The research and development and preparation method of doped TiO2 as an anti-ultraviolet filler are of great significance for extending the weather resistance of composite insulators, and can provide key support for the reliability of outdoor operation of power systems.

[0028] According to an embodiment of one aspect of the above-mentioned inventive concept, an anti-UV filler is provided, the component of the anti-UV filler is Fe-doped TiO2; the particle size of the anti-UV filler is 30 to 50 nm; wherein, in the anti-UV filler, the molar ratio of iron element to titanium element is in the range of (0.2 to 2):100.

[0029] The anti-ultraviolet filler of the embodiment of the present invention has strong stability and excellent electrical and mechanical properties; and can improve the anti-ultraviolet aging ability of silicone rubber.

[0030] In some embodiments of the present invention, the anti-ultraviolet filler is a strong anti-ultraviolet filler Fe-doped TiO2, wherein the Fe element exists in the form of trivalent iron in the strong anti-ultraviolet filler.

[0031] In some embodiments of the present invention, the method for preparing a strong UV-resistant filler comprises the following steps:

[0032] (1) Add glacial acetic acid, anhydrous ethanol and deionized water in a volume ratio of (7-8):(4-5):1, for example, 7.1:4.2:1, 7.2:4.3:1, 7.4:4.4:1, 7.6:4.5:1, 7.8:4.6:1, 7.9:4.8:1, etc., to a beaker, stir evenly by electromagnetic for 0.5-1h, and then add a certain amount of ferric nitrate according to the Fe / Ti molar concentration ratio of (0.2-2):100, for example, the molar ratio can be 0.36:17, 0.42:36, 0.68:48, 1.3:64, 1.6:78, 1.9:96, etc., to obtain a first solution. Liquid A; wherein the concentration of iron in the first solution is 0.0004-0.6 mol / L, for example, it can be 0.0004 mol / L, 0.00048 mol / L, 0.00098 mol / L, 0.0013 mol / L, 0.0067 mol / L, 0.019 mol / L, 0.036 mol / L, 0.048 mol / L, 0.068 mol / L, 0.089 mol / L, 0.14 mol / L, 0.23 mol / L, 0.31 mol / L, 0.42 mol / L, 0.53 mol / L, 0.59 mol / L, etc.

[0033] (2) titanate and anhydrous ethanol are mixed in a volume ratio of (1:6) to (3:6), for example, 1.3:6, 1.8:6, 2.1:6, 2.3:6, 2.8:6, etc.; after electromagnetically stirring for 0.5 to 1 hour, a second solution B is obtained;

[0034] (3) adding the first solution A obtained in step (1) to the second solution B obtained in step (2) at a uniform speed and stirring until a uniform and transparent TiO2 sol is formed, and aging the solution at room temperature for 20 to 24 hours to obtain a gel. For example, the aging time may be 20.8 hours, 21.3 hours, 22.8 hours, 23.4 hours, 23.9 hours, etc.;

[0035] (4) drying the gel obtained in step (3) at 50-80° C. (for example, 52° C., 59° C., 64° C., 71° C., 78° C., etc.) for 24-36 hours (for example, 25.9 h, 29.8 h, 32.6 h, 34.8 h, 35.9 h, etc.); then grinding the gel into powder, and sintering at 900-1000° C. (for example, 912° C., 936° C., 958° C., 982° C., 998° C., etc.) ) conditions for high temperature calcination for 2 to 4 hours (for example, it can be 2.1h, 2.8h, 3.1h, 3.4h, 3.9h, etc.), cooled with the furnace, and finally fully ground to obtain Fe-TiO2 powder with strong anti-ultraviolet filler, and then the particle size is screened by a vibration screen, and the maximum particle size is controlled at 30 to 50nm (for example, the particle size of the anti-ultraviolet filler can be 31nm, 37nm, 43nm, 46nm, 47nm, 49nm, etc.).

[0036] According to an embodiment of the present invention, a method for preparing the above-mentioned anti-UV silicone rubber is provided, and the method for preparing the anti-UV silicone rubber comprises: mixing methyl vinyl silicone raw rubber, aluminum hydroxide powder and fumed silica to obtain a mixed base rubber; mixing the mixed base rubber, anti-UV filler, hydrogen-containing silicone oil and a coupling agent to obtain a mixed rubber; subjecting the mixed rubber to a vulcanizing agent for a vulcanization reaction to obtain the anti-UV silicone rubber; wherein the anti-UV filler is the above-mentioned anti-UV filler or an anti-UV filler obtained by the above-mentioned preparation method.

[0037] In some embodiments of the present invention, the UV-resistant silicone rubber is a strong UV-resistant silicone rubber.

[0038] In some embodiments of the present invention, the raw materials for preparing the highly anti-ultraviolet silicone rubber include a silicone rubber base material and a highly anti-ultraviolet filler, and the component of the highly anti-ultraviolet filler is Fe-doped TiO2.

[0039] In some embodiments of the present invention, the silicone rubber matrix material includes methyl vinyl silicone rubber, fumed silica, aluminum hydroxide powder, silicone oil, coupling agent KH560, and vulcanizing agent.

[0040] In some embodiments of the present invention, the method for preparing the highly UV-resistant silicone rubber comprises the following steps:

[0041] (1) adding methyl vinyl silicone rubber, aluminum hydroxide powder and meteorological white carbon black into a kneader according to a proportion and mixing, controlling the temperature to 135-160° C. (for example, 139° C., 142° C., 146° C., 151° C., 158° C., etc.), and continuously mixing for 3-5 hours (for example, 3.1 hours, 3.7 hours, 4.2 hours, 4.6 hours, 4.9 hours, etc.) to obtain a mixed base rubber;

[0042] (2) adding the mixed base rubber obtained in step (1), strong anti-ultraviolet filler (Fe-TiO2), silicone oil, and coupling agent KH560 into a kneader, controlling the temperature to 140-160° C. (for example, 141° C., 149° C., 151° C., 154° C., 159° C., etc.), and continuously mixing for 2-3 h (for example, the time may be 2.1 h, 2.3 h, 2.4 h, 2.6 h, 2.9 h, etc.) to obtain a mixed rubber;

[0043] (3) After cooling the mixed rubber obtained in step (2) for 24 to 36 hours, the dipentadienyl vulcanizer is evenly added to the mixed rubber, and the mixed rubber is subjected to open mixing for 10 to 15 minutes (for example, 10.9 minutes, 11.8 minutes, 12.9 minutes, 13.8 minutes, 14.6 minutes, etc.) to obtain a highly UV-resistant silicone rubber, wherein the sample preparation conditions are: pressure 10 to 15 MPa (for example, 10.3 MPa, 11.9 MPa, 12.6 MPa, 13.4 MPa, 14.8 MPa, etc.), temperature 140 to 160°C (for example, 143°C, 148°C, 152°C, 156°C, 158°C, etc.), and vulcanization time 10 to 15 minutes (for example, 10.8 minutes, 11.7 minutes, 12.8 minutes, 13.6 minutes, 14.9 minutes, etc.).

[0044] In some embodiments of the present invention, the preparation method of strong UV resistant silicone rubber includes the following raw materials in parts by weight: 5 to 10 parts of strong UV resistant filler (Fe-TiO2), 75 to 110 parts of methyl vinyl silicone rubber, 25 to 45 parts of fumed silica, 110 to 140 parts of aluminum hydroxide powder, 1 to 3 parts of hydrogenated silicone oil, 1 to 5 parts of coupling agent KH560, and 1 to 3 parts of dipentadienyl vulcanizing agent. For example, the strong anti-UV filler can be 5.3 parts, 6.1 parts, 7.2 parts, 8.6 parts, 9.1 parts, etc.; the methyl vinyl silicone rubber can be 76 parts, 83 parts, 91 parts, 102 parts, 109 parts, etc.; the fumed silica can be 26 parts, 29 parts, 32 parts, 39 parts, 44 parts, etc.; the aluminum hydroxide powder can be 113 parts, 119 parts, 124 parts, 132 parts, 139 parts, etc.; the hydrogenated silicone oil can be 1.3 parts, 1.6 parts, 1.9 parts, 2.3 parts, 2.9 parts, etc.; for example, the coupling agent can be 1 part, 2 parts, 3 parts, 4 parts, 4.9 parts, etc.; the vulcanizing agent can be 1.1 parts, 1.4 parts, 1.8 parts, 2.1 parts, 2.8 parts, etc.

[0045] In some embodiments of the present invention, the particle size of the strong anti-UV filler (Fe-TiO2) is 30-50nm. For example, the particle size of the anti-UV filler can be 32nm, 34nm, 36nm, 41nm, 46nm, 47nm, etc.

[0046] In some embodiments of the present invention, the molecular weight of the methyl vinyl silicone rubber is 600,000 to 660,000, and the vinyl content is 0.16 to 0.22%. For example, the molecular weight of the methyl vinyl silicone rubber can be 600,000, 610,000, 620,000, 630,000, 640,000, 650,000, etc., and the vinyl content is 0.16 to 0.22%, for example, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, etc.

[0047] In some embodiments of the present invention, the specific surface area of ​​the fumed silica in the raw material is 220 to 250 m 3 / g. For example, the specific surface area of ​​fumed silica is 223m 3 / g, 231m 3 / g, 239m 3 / g, 243m 3 / g, 249m 3 / g, etc.

[0048] In some embodiments of the present invention, the particle size of the aluminum hydroxide powder is 6000-7000 mesh. For example, the particle size of the aluminum hydroxide powder is 6129 mesh, 6316 mesh, 6489 mesh, 6592 mesh, 6876 mesh, 6989 mesh, etc.

[0049] In some embodiments of the present invention, the hydrogen-containing silicone oil is a hydrogen-containing silicone oil with a hydrogen concentration greater than 0.5%, for example, the hydrogen-containing silicone oil has a hydrogen concentration of 0.6%, 0.63%, 0.71%, 0.79%, 0.92%, etc.

[0050] In some embodiments of the present invention, the concentration of coupling agent KH560 is greater than 95%. For example, the concentration of coupling agent KH560 is 96.3%, 96.9%, 97.2%, 98.1%, 99.3%, etc.

[0051] In some embodiments of the present invention, the concentration of the dipentadienyl vulcanizing agent is between 93% and 96.5%. For example, the concentration of the dipentadienyl vulcanizing agent is 93.1%, 93.9%, 94.3%, 95.1%, 96.3%, etc.

[0052] In order to further illustrate the effect of the present invention, specific embodiments are used for illustration below.

[0053] All reagents used in the following examples and comparative examples are commercially available reagents.

[0054] Example 1

[0055] (1) Preparation of UV-resistant fillers

[0056] Add glacial acetic acid, anhydrous ethanol and deionized water in a volume ratio of 7:4:1 to a beaker, stir evenly by electromagnetic for 1 hour, then add a certain amount of ferric nitrate according to the Fe / Ti molar concentration ratio of 1.2% to obtain the first solution A; then stir evenly by electromagnetic for 1 hour by butyl titanate and anhydrous ethanol in a volume ratio of 1:6 to obtain the second solution B; slowly drop the first solution A into the second solution B at a uniform speed and stir until a uniform and transparent TiO2 sol is formed, and age at room temperature for 24 hours to obtain a gel material; dry the gel at 50°C for 24 hours. Grind the gel into powder, calcine at 950°C for 3 hours, cool with the furnace, and finally grind it fully to obtain Fe-TiO2 powder strong anti-ultraviolet filler, and then screen the particle size through a vibrating screen, and the maximum particle size is controlled at 30-50nm. Prepare Fe-doped TiO2 strong anti-ultraviolet filler.

[0057] (2) UV-resistant silicone rubber

[0058] The highly UV-resistant silicone rubber of this embodiment is made by cross-linking the following raw materials in parts by mass:

[0059] 100 parts (10 kg) of methyl vinyl rubber with a molecular weight of 660,000 and a vinyl content of 0.16%, 35 parts (3.5 kg) of fumed silica, 120 parts (12 kg) of aluminum hydroxide micropowder, 3 parts (0.3 kg) of hydrogen-containing silicone oil with a hydrogen content of 0.5%, 1 part (0.1 kg) of coupling agent KH560 with a concentration of 95%, 1 part (0.1 kg) of dipentadienyl vulcanizing agent with a concentration of 95%, 2 parts (0.2 kg) of nano zinc oxide, 2 parts (0.2 kg) of iron oxide, and 5 parts (0.5 kg) of iron co-doped titanium dioxide strong anti-ultraviolet filler prepared in step (1).

[0060] The specific preparation steps are as follows:

[0061] According to the above raw material ratio, methyl vinyl silicone raw rubber, aluminum hydroxide powder and fumed silica are first added to a kneader for mixing, the temperature is controlled at 140°C, and the mixing is continued for 3 hours to obtain a mixed base rubber; the mixed base rubber, the strong UV resistant filler iron co-doped titanium dioxide (Fe-TiO2) prepared in step (1), silicone oil, and coupling agent KH560 are added to a kneader, the temperature is controlled at 140°C, and the mixing is continued for 3 hours to obtain a mixed rubber; after the mixed rubber is cooled for 24 hours, a dipentadienyl vulcanizer is evenly dripped on the mixed rubber, and the mixed rubber is refined on an open mill for 10 minutes to obtain a strong UV resistant silicone rubber; the sample preparation conditions are: pressure of 2 MPa, temperature of 140°C, and vulcanization time of 10 minutes, to obtain a silicone rubber material prepared by a strong UV resistant formula and preparation process.

[0062] Comparative Example 1

[0063] The ordinary silicone rubber of this comparative example is made by cross-linking the following raw materials in parts by weight:

[0064] 100 parts (10kg) of methyl vinyl raw rubber with a molecular weight of 660,000 and a vinyl content of 0.16%, 35 parts (3.5kg) of fumed silica, 120 parts (12kg) of aluminum hydroxide powder, 3 parts (0.3kg) of hydrogen-containing silicone oil with a hydrogen content of 0.5%, 1 part (0.1kg) of coupling agent KH560 with a concentration of 95%, 1 part (0.1kg) of dipentadienyl vulcanizer with a concentration of 95%, 2 parts (0.2kg) of nano zinc oxide, and 2 parts (0.2kg) of iron oxide.

[0065] The specific preparation steps are as follows:

[0066] According to the above raw material ratio, methyl vinyl silicone raw rubber, aluminum hydroxide powder and fumed silica are first added into a kneader and mixed, the temperature is controlled at 140°C, and the mixing is continued for 3 hours to obtain a mixed base rubber; the mixed base rubber, nano zinc oxide, iron oxide, silicone oil and coupling agent KH560 are added into a kneader, the temperature is controlled at 140°C, and the mixing is continued for 3 hours to obtain a mixed rubber; after the mixed rubber is cooled for 24 hours, the dipentadienyl vulcanizer is evenly dripped on the mixed rubber, and the mixed rubber is refined on an open mill for 10 minutes to obtain a highly UV-resistant silicone rubber; the sample preparation conditions are: pressure 12MPa, temperature 140°C, and vulcanization time 10 minutes, to obtain a silicone rubber material prepared by a conventional formula and preparation process.

[0067] Comparative Example 2

[0068] The anti-ultraviolet silicone rubber of this comparative example is made by cross-linking the following raw materials in parts by weight:

[0069] 100 parts (10kg) of methyl vinyl raw rubber with a molecular weight of 660,000 and a vinyl content of 0.16%, 35 parts (3.5kg) of fumed silica, 120 parts (12kg) of aluminum hydroxide powder, 3 parts (0.3kg) of hydrogen-containing silicone oil with a hydrogen content of 0.5%, 1 part (0.1kg) of coupling agent KH560 with a concentration of 95%, 1 part (0.1kg) of dipentadienyl vulcanizer with a concentration of 95%, and 5 parts (0.5kg) of titanium dioxide.

[0070] According to the above raw material ratio, methyl vinyl silicone raw rubber, aluminum hydroxide powder and fumed silica are first added into a kneader and mixed, the temperature is controlled at 140°C, and the mixing is continued for 3 hours to obtain a mixed base rubber; the mixed base rubber, titanium dioxide, silicone oil and coupling agent KH560 are added into a kneader, the temperature is controlled at 140°C, and the mixing is continued for 3 hours to obtain a mixed rubber; after the mixed rubber is cooled for 24 hours, the dipentadienyl vulcanizer is evenly dripped on the mixed rubber, and the mixed rubber is refined on an open mill for 10 minutes to obtain a strongly UV-resistant silicone rubber. The sample preparation conditions are: pressure 12MPa, temperature 140°C, and vulcanization time 10 minutes, and a silicone rubber material prepared by a conventional UV-resistant formula and preparation process is obtained.

[0071] Performance Testing

[0072] The 14×12×2 mm silicone rubber samples prepared in Comparative Example 1, Comparative Example 2, and Example 1 were subjected to UV accelerated tests, and electrical and mechanical performance tests were performed in accordance with relevant standards. The UV accelerated conditions and UV aging conditions were: temperature of 50°C, irradiation intensity of 313 UVB light source of 0.79 W / m 2 The UV aging time is 500h. The test results are shown in Table 1 and Table 2.

[0073] Table 1 Performance test results of silicone rubber samples of Example 1 and Comparative Examples 1-2

[0074]

[0075] Table 2 500h UV aging performance test results of silicone rubber samples of Example 1 and Comparative Examples 1-2

[0076]

[0077] According to the data analysis in Table 1 and Table 2, the following conclusions can be drawn:

[0078] (1) After ultraviolet accelerated aging, the electrical and mechanical properties of the silicone rubber samples prepared in Example 1, Comparative Example 1 and Comparative Example 2 were significantly reduced, but the reduction in Comparative Example 1 and Comparative Example 2 was greater than that in Example 1. Among them, the surface resistivity decreased by 2.2% in Comparative Example 1, 1.2% in Comparative Example 2, and 0.8% in Example 1. The elongation at break decreased by 25.6% in Comparative Example 1, 16.2% in Comparative Example 2, and 12.2% in Example 1. It can be seen that the anti-ultraviolet silicone rubber of the embodiment of the present invention can effectively improve the anti-ultraviolet aging ability of silicone rubber, and the performance retention rate of the prepared strong anti-ultraviolet silicone rubber is relatively high.

[0079] (2) The highly UV-resistant silicone rubber of the embodiment of the present invention has strong stability, excellent electrical and mechanical properties, and an intact surface without any damage.

[0080] (3) The strong UV-resistant silicone rubber of the embodiment of the present invention has strong stability, and its electrical and mechanical properties meet the requirements of DL376-2019. Under 500h UV accelerated aging conditions, the performance degradation rate is greatly reduced, the UV resistance is excellent, the preparation process is simple, convenient and efficient, easy to promote, and conducive to long-term outdoor use.

[0081] In summary, the main component of the anti-ultraviolet filler used in the anti-ultraviolet silicone rubber of the present invention is Fe-doped TiO2; specifically, through specific preparation steps, including solution preparation, sol formation, gel drying, high-temperature calcination and particle size screening, Fe-doped TiO2 (Fe-TiO2) powder with a particle size controlled at 30 to 50 nm is obtained. This strong anti-ultraviolet filler is mixed with raw materials such as methyl vinyl silicone rubber, fumed silica, aluminum hydroxide powder, hydrogen-containing silicone oil, coupling agent KH560 and di-2-5 vulcanizing agent in a certain proportion, and after kneading, cooling and vulcanization and other process steps, a silicone rubber with excellent anti-ultraviolet performance is prepared. The silicone rubber material not only significantly improves the anti-ultraviolet ability, but also maintains good mechanical and electrical properties, and is suitable for composite insulators in outdoor environments, effectively extending their service life. The preparation method of the present invention is simple and efficient, and is suitable for large-scale industrial production.

[0082] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0083] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments described herein, but should conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. An anti-ultraviolet filler, characterized in that: The component of the anti-ultraviolet filler is Fe-doped TiO2; The particle size of the anti-ultraviolet filler is 30 to 50 nm; Wherein, in the anti-ultraviolet filler, the molar ratio of iron element to titanium element is in the range of (0.2-2):

100.

2. A method for preparing the anti-ultraviolet filler according to claim 1, characterized in that: The preparation method of the anti-ultraviolet filler comprises: adding a soluble iron salt into a mixed solvent of glacial acetic acid, anhydrous ethanol and deionized water to obtain a first solution; Mixing butyl titanate and anhydrous ethanol evenly to obtain a second solution; The first solution is added dropwise to the second solution and stirred until a uniform and transparent TiO2 sol is formed, and then aged at room temperature to obtain a gel; The gel is dried and calcined to obtain an anti-ultraviolet filler.

3. The method for preparing the anti-ultraviolet filler according to claim 2, characterized in that: The molar ratio of the iron element in the soluble iron salt to the titanium element in the butyl titanate is (0.2-2):100; And / or, in the first solution, the volume ratio of glacial acetic acid, anhydrous ethanol and deionized water is in the range of (7-8):(4-5):1; and / or, the concentration of the iron element in the soluble iron salt in the first solution is 0.0004-0.6 mol / L; And / or, in the second solution, the volume ratio of butyl titanate to anhydrous ethanol is (1:6) to (3:6).

4. The preparation method according to claim 2 or 3, characterized in that: The soluble iron salt is ferric nitrate or ferric chloride; And / or, the aging time is 20 to 24 hours; And / or, the gel is dried under the following conditions: drying at 50-80° C. for 24-36 hours; And / or, the calcination condition is: calcination at 900-1000° C. for 2-4 hours.

5. A UV-resistant silicone rubber, characterized in that: The anti-ultraviolet silicone rubber comprises the anti-ultraviolet filler according to claim 1 or the anti-ultraviolet filler obtained by the preparation method according to any one of claims 2 to 4.

6. The UV-resistant silicone rubber according to claim 5, characterized in that: The raw materials for preparing the anti-ultraviolet silicone rubber include, by weight: 5-10 parts of anti-ultraviolet filler, 75-110 parts of methyl vinyl silicone rubber, 25-45 parts of fumed silica, 110-140 parts of aluminum hydroxide powder, 1-3 parts of hydrogen-containing silicone oil, 1-5 parts of coupling agent and 1-3 parts of vulcanizing agent.

7. The UV-resistant silicone rubber according to claim 6, characterized in that: The vulcanizing agent is a dipentadienyl vulcanizing agent; And / or, the coupling agent is KH560; And / or, the molecular weight of the methyl vinyl silicone rubber is 600,000 to 660,000, and the vinyl content is 0.16 to 0.22%; And / or, the specific surface area of ​​the fumed silica is 220 to 250 m 3 / g; And / or, the particle size of the aluminum hydroxide micropowder is 6000-7000 mesh; And / or, the hydrogen concentration of the hydrogen-containing silicone oil is greater than 0.5%.

8. A method for preparing the UV-resistant silicone rubber according to claim 6, characterized in that: The preparation method of the anti-ultraviolet silicone rubber comprises: Mixing methyl vinyl silicone rubber, aluminum hydroxide powder and fumed silica to obtain a mixed base rubber; The mixed base glue, anti-ultraviolet filler, hydrogen-containing silicone oil and coupling agent are mixed to obtain a mixed glue; The mixed rubber and the vulcanizing agent are subjected to a vulcanization reaction to obtain the UV-resistant silicone rubber; Wherein, the anti-ultraviolet filler is the anti-ultraviolet filler according to claim 1 or the anti-ultraviolet filler obtained by the preparation method according to any one of claims 2 to 4.

9. The method for preparing the UV-resistant silicone rubber according to claim 8, characterized in that: The method of mixing the methyl vinyl silicone rubber, aluminum hydroxide powder and fumed silica is to knead them with a kneader at a temperature of 135 to 160° C. and a kneading time of 3 to 5 hours; And / or, the mixed base rubber, anti-ultraviolet filler, hydrogen-containing silicone oil and coupling agent are mixed by kneading with a kneader at a temperature of 140 to 160° C. for 2 to 3 hours; And / or, the pressure of the mixed rubber and the vulcanizing agent for vulcanization reaction is 10-15 MPa, the temperature is 140-160° C., and the time is 10-15 min.

10. Use of the UV-resistant silicone rubber according to any one of claims 5 to 7 or the UV-resistant silicone rubber obtained by the preparation method of the UV-resistant silicone rubber according to claim 8 or 9 in preparing a composite insulator.

Citation Information

Patent Citations

  • Process for preparing iron-doped titanium dioxide powders

    CN102592836A

  • High temperature resistant and low contraction permanent deformation self-precipitated oil rubber compound and preparation method thereof

    CN110922763A

  • Ultrahigh heat-resistant silicone rubber and preparation method thereof

    CN113956668A

  • Divalent iron ion doped black titanium dioxide nanosheet and preparation method thereof

    CN115845849A

  • Anti-ultraviolet aging silicone rubber composition, silicone rubber and preparation method and application thereof

    CN116694084A